Arms Proliferation and Militancy in Rivers State, Nigeria: A Comparative Study of Amaechi and Wike’s Administrations - Nweke, Kenneth; Etido-Inyang, Eunice (Advances in Social Sciences Research Journal, 2020)
This research examined the nature of arms proliferation and militancy in the administrations of Governors Chibiuke Rotimi Amaechi and Ezenwo Nyesom Wike in Rivers State, Nigeria. The objectives were to determine the nature of arms proliferation and militancy in Rivers State in the two administrations. This research became necessary owing to the increasing rate of insecurity in Rivers State. The inability of security agencies to mitigate the security challenges confronting the State and the politicisation of the security of the State makes this research inevitable. Two key areas of concerns were discernable. First, the proliferation of Small Arms and Light Weapons (SALW) in the State has led to militancy of destructive proportion. Second, arms proliferation and militancy have undermined socio-economic and political development of the people of the State. The security challenges arising, therefore, have created an inhabitable state triggered by fear, intimidation, armed robbery, assassinations, cultism, kidnapping for ransom, arms smuggling, political thuggery, electoral violence, intimidation and destruction of lives and property across the 23 local government areas of the State. The Frustration-Aggression theory and the Realist Theory were used to establish a correlation between arms proliferation and militancy, on one hand, and deprivation, marginalisation, environmental degradation and lack of physical and human capital development for sustainable livelihood of the people of Rivers State which triggered arms proliferation and militancy in the state, on the other hand. This study used descriptive research design to examine the nature and justification, through psychological approach of comparison, of arms proliferation and militancy in both Amaechi and Wike’s administrations. A trend analysis, through historical investigation, was also used to determine the nature of arms proliferation and militancy prior to Amaechi’s administration in 2007. Secondary data were mostly used. Through content analysis and review of relevant literature, this research observed that the upsurge of arms proliferation and militancy in Rivers State started as part of the agitation for resource control and self-determination of the Niger Delta people. Redistribution of arms to political thugs and cultists after the 2009 Federal Government’s Amnesty which has made elections in Rivers State nasty, bloody and brutal, and lives useless and short, instigated the new waves of arms proliferation and militancy in Rivers State under Amaechi and Wike’s administrations. This research concluded that unless there are conscious efforts by the State Actors to comprehensively mop-up of arms and ammunition in Rivers State and bring pepertrators of these heinous crimes to book, the search for peace, stability, and security of lives and property of Rivers State people and residents alike would be too far to realise.